Toward painless road-cycling for women: Innovative pressure distribution through lattice-based seat pads - Nispel, K.; Schubert, N.; Senner, V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Potential health risks for male athletes in professional road cycling are numerously investigated. For female athletes, necessary information is missing and thus there is a lack of equipment meeting their specific needs. The different pelvic anatomy of women compared to men suggests different saddle designs, different cycling short pads, and even different types of material to avoid pain and health problems. To collect data for a systematic development of pads specifically for women, we performed a study with 29 ambitious female athletes, who road cycle long distances (>90 min) at least once a week. First, we documented each athlete`s recent cycling situation, including the perceived comfort, grievances and the equipment used. Second, molds of the pelvis-saddle interfaces were generated using a previously developed measurement saddle to analyze pressure distributions during both static and dynamic loading. Measures were taken using the idmatch system following a bike fitting, which suggested a bicycle setup incorporating, among other factors, the individual athlete`s anthropometric data. Molds were subsequently digitized with a calibrated 3D scanner. Third, the digital pressure data resulting from the molds was analyzed considering its ability to represent interindividual differences, which validated the developed measurement saddle. Finally, a novel lattice-based pad prototype was designed based on the measured pressure data. Finite element analyses (FEA) were carried out to observe mechanical loads in the lattice structure and enable an optimization of the design. The prototype was additively manufactured using stereolithography (SLA).